Women in the dairy family farmer: analysis of uruguayan and french situations - Courdin, Virginia; Dufour, Annie; Dedieu, Benoit (Agrociencia Uruguay, 2010)
The aim of this study was to characterize different aspects of women’s work at dairy family farms in France and Uruguay, from the analysis of practices and theirs representations. A study of 20 cases of women was carried out (10 in Uruguay and 10 in France), using semi-structured interviews, that later were re-transcribed for the thematic analysis of content. The results revealed that the familiar dairy farming involve an homogeneous participation of women work, with the main difference between studied countries in the gender status in the society and professional level of the women. Women from both countries carry out mainly the milking, the care of calves and the administrative work, varying their degree of responsibility. Their role in the work group can be assigned, delegated or chosen. The constructed compromise as a whole, can vary between strong (be responsible for tasks, active participation in decisions and chosen role) and weak (little participation in the tasks and little exchange of information). The diversity of compromise is related to the joint between familiar, professional and social universe, offering to the women a space of autonomy in time management and task accomplishment. These factors are important in the construction of an identity of their own.